Framework development of Yi traditional craft cultural factors on culture-centered design in Liangshan, China - Bu, Jimo (2024)
The traditional craft culture of the Yi ethnic group has exhibited a tendency towards decline and transformation in various aspects due to the impacts of industrial modernization. Although people are interested in buying Yi cultural artefacts, they have limited practical use and lack diversity. The design developments of new products need to be maintained by preserving the Yi traditional crafts. In the context of a new cultural environment, the Yi traditional crafts have a more important impact on the acceptance of related development of products, designs and services. Although the Yi traditional craft has been widely discussed in recent years, the available documentation does not provide extensive knowledge about the integration of Yi crafts on designs. In fact, there is still a lack of research in the relationship between Yi traditional crafts and the designs of cultural products. Consequently, local designers are in dilemma without proper references when integrating the Yi cultural factors into their designs. Therefore, local designers make mistakes in explaining the cultural attributes on designs, as their designs touch superficially on the surface of culture. This study shows that local designers lack an in-depth understanding of the Yi craft field. A rigorous study of the tangible and intangible culture of Yi traditional crafts can help designers obtain a new paradigm in the designs of products for Yi crafts. Thus, the purpose of this study is to determine the prominent Yi Traditional Craft Cultural Factors (YTCCF) and their attributes to develop a framework that influences Chinese cultural products. A mixed-method was employed in this study. In the first phase, three groups were used in the Nominal Group Techniques (NGTs) to discuss the Yi Traditional Craft Cultural Factors (YTCCF), and explain the reasons for their factors. Then, the findings of Nominal Group Technique (NGT) were used to conduct a comprehensive participant survey to comprehend the prominent factors and attributes of Yi Traditional Craft Cultural Factors (YTCCF). Then statistical analysis was conducted to establish the usability evaluation. The results of the survey reconfirmed the five factors that influenced the designs the Yi craft products and also determined their 15 prominent attributes. Finally, these factors and attributes were validated by the Yi designers. The contributions of this study can help to increase the understanding of the culture Yi traditional crafts and provide an approach to explore the transition to modern designs. A framework of Yi Traditional Craft Culture Factors (YTCCF) was also developed to generate Yi culture-centered designs. Designers and stakeholders can use the results as a flexible guide to create localized innovative designs.